The nonlinear least square fitting for rotation curve of orion dwarf spiral - Hashim, N.; Abidin, Z.Z.; Ibrahim, U.F.S.U.; Hassan, M.S.R.; Hamidi, Z.S.; Umar, R.; Ibrahim, Z.A. (Universiti Kebangsaan Malaysia, 2015)
The basis of the nonlinear least square fitting is to fit the nonlinear rotation curve model with the observed rotation curve of the Orion dwarf galaxy. It has been the most powerful tool to study the distribution of dark matter in galaxies where it is used to obtain the proper mass model of a galaxy. In this paper, we present the rotation curve fit of Orion dwarf galaxy, corrected for asymmetric drift by using the gradient method of nonlinear least square. Our results showed an excellent agreement between the mass models of cored halo profile with the observed rotation curve. Thus, we can estimate the value of disk mass, MD; the core radius, r0 and core density, ro of the galaxy with 1-s of uncertainty. We finally indicated the dark matter halo distribution as cored dark matter halo with density, 3.9 × 106MŸ kpc-3.